The importance of in-year seasonal fluctuations for biomonitoring of apex predators: A case study of 14 essential and non-essential elements in the liver of the common buzzard (Buteobuteo) in the United Kingdom. (15th April 2023) - Ozaki, Shinji; Movalli, Paola; Cincinelli, Alessandra; Alygizakis, Nikiforos; Badry, Alexander; Chaplow, Jacqueline S.; Claßen, Daniela; Dekker, René W.R. J.; Dodd, Beverley; Duke, Guy; Koschorreck, Jan; Pereira, M. Glória; et al.
Abstract: Trace elements are chemical contaminants spread in the environment by anthropogenic activities and threaten wildlife and human health. Many studies have investigated this contamination in apex raptors as sentinel birds. However, there is limited data for long-term biomonitoring of multiple trace elements in raptors. In the present study, we measured the concentrations of 14 essential and non-essential trace elements in the livers of the common buzzard ( But eo buteo ) collected in the United Kingdom from 2001 to 2019 and investigated whether concentrations have changed during this period. In addition, we estimated the importance of selected variables for modelling element accumulations in tissues. Except for cadmium, hepatic concentrations of harmful elements in most buzzards were lower than the biological significance level of each element. Hepatic concentrations of certain elements, including lead, cadmium, and arsenic, varied markedly seasonally within years. Their peak was in late winter and trough in late summer, except copper which showed an opposite seasonal pattern. In addition, lead in the liver consistently increased over time, whereas strontium showed a decreasing trend. Hepatic concentrations of cadmium, mercury, and chromium increased with age, whereas selenium and chromium were influenced by sex. Hepatic concentrations of arsenic and chromium also differed between different regions. Overall, our samples showed a low risk of harmful effects of most elements compared to the thresholds reported in the literature. Seasonal fluctuation was an important descriptor of exposure, which might be related to the diet of the buzzard, the ecology of their prey, and human activities such as the use of lead shot for hunting. However, elucidating reasons for these observed trends needs further examination, and biomonitoring studies exploring the effects of variables such as age, sex, and seasonality are required. Graphical abstract: Image 1 Highlights: Liver Pb, Cd, As, Se, Cu, and Co fluctuated seasonally within a year. Fluctuation peak was in late winter and trough in late summer, except for Cu. Liver Pb increased over the monitoring period. Body and liver weights were negatively correlated with liver essential elements. Relative importance of variables for predictive models of metal burden was estimated.